SHARIA SUPERVISORY BOARD, BOARD ATTRIBUTES AND REAL EARNINGS MANAGEMENT IN ISLAMIC BANKS - Musa, Sulaiman; Haji Masri, Masairol; binti Hamdan, Mahani (Journal of Islamic Monetary Economics and Finance, 2025)
This study examines how the Sharia Supervisory Board (SSB) moderates the effects of Board of Directors (BOD) characteristics on real earnings management (REM) of Islamic banks. Using unbalanced data encompassing 45 Islamic banks across 15 countries from 2012 to 2023, it documents a negatively significant influence of board size, independence, and expertise on REM. The influence of board's diligence, however, is absent. The study further notes that the SSB index moderates the effect of BOD attributes on REM in Islamic banks. The findings hold important implications for policymakers and regulators in shaping regulations on SSB and BOD oversight functions to curb REM practices. The study also contributes to the literature by offering further empirical evidence on the relationship between corporate governance and REM in Islamic banks.